Crashing. The complete third season [videorecording (DVD)] - Holmes, Pete, 1979- (Crashing (Television program : 2017- ), 2019)
Fresh off of his two-month college comedy tour, Pete returns to New York City with newfound confidence in his comedic abilities. While growing more assured, he continues to struggle over what he really wants out of comedy and how to find a happy balance between his old, faith-based self and the new, more ambitious comic he's becoming.